1995
DOI: 10.1002/1097-4679(199509)51:5<676::aid-jclp2270510513>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Comparative concurrent validities of five alcoholism measures in a psychiatric hospital

Abstract: The concurrent validities of five self‐report alcoholism measures were compared in a psychiatric hospital population using Diagnostic Interview Schedule (DIS) alcohol dependence module outputs as criterion. The Michigan Alcohol Screening Test was the most accurate identifier of alcohol dependence at some point in the subjectS' life, while the CAGE interview best identified alcohol dependence in the previous year. The correlations of a quantity‐frequency measure, the Clinical Signs checklist, and the Medical Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Validity analyses included both external (convergent) and internal (structural) elements of the MAST scores. Convergent validity results presented a wide range of correlations (r = .01 to r = .95) across 45 substance use instruments (see Table 2), with the majority of convergent instruments having large effect sizes according to criteria set by Lipsey Systematic Review of the Michigan Alcoholism Screening Test Saltstone et al, 1994;Stover, Hall, et al, 2012;Stover, Urdahl, et al, 2012;Taylor & Kliewer, 2006;Teslak, 2000Drake et al, 1990Lee & DeFrank, 1988;Myerholtz & Rosenberg, 1997;Teslak, 2000;Watson et al, 1995;Wilson et al, 1988Barry & Fleming, 1993Bohn et al, 1995;Conley, 2001Barry & Fleming, 1993Barry & Fleming, 1993Barry & Fleming, 1993Gorelick et al, 1990Lee & DeFrank, 1988Forbey et al, 2012Myerholtz & Rosenberg, 1997Forbey et al, 2012Forbey et al, 2012Isaak et al, 2011Hunter, 2007Hunter, 2007Hunter, 2007Roque, 2006Westermeyer et al, 2004Greene, 2002Myerholtz & Rosenberg, 1997;Young, 2005Young, 2005Follman, 2012Teslak, 2000;Young, 2005Follman, 2012Teslak, 2000;…”
Section: Discussionmentioning
confidence: 99%
“…Validity analyses included both external (convergent) and internal (structural) elements of the MAST scores. Convergent validity results presented a wide range of correlations (r = .01 to r = .95) across 45 substance use instruments (see Table 2), with the majority of convergent instruments having large effect sizes according to criteria set by Lipsey Systematic Review of the Michigan Alcoholism Screening Test Saltstone et al, 1994;Stover, Hall, et al, 2012;Stover, Urdahl, et al, 2012;Taylor & Kliewer, 2006;Teslak, 2000Drake et al, 1990Lee & DeFrank, 1988;Myerholtz & Rosenberg, 1997;Teslak, 2000;Watson et al, 1995;Wilson et al, 1988Barry & Fleming, 1993Bohn et al, 1995;Conley, 2001Barry & Fleming, 1993Barry & Fleming, 1993Barry & Fleming, 1993Gorelick et al, 1990Lee & DeFrank, 1988Forbey et al, 2012Myerholtz & Rosenberg, 1997Forbey et al, 2012Forbey et al, 2012Isaak et al, 2011Hunter, 2007Hunter, 2007Hunter, 2007Roque, 2006Westermeyer et al, 2004Greene, 2002Myerholtz & Rosenberg, 1997;Young, 2005Young, 2005Follman, 2012Teslak, 2000;Young, 2005Follman, 2012Teslak, 2000;…”
Section: Discussionmentioning
confidence: 99%
“…Each item is scored 0 or 1, with scores of 10 or more indicating evidence of having had a severe drinking problem at some point in one's life. The MAST has been found to have higher concurrent validity when compared to other alcoholism measures with reference to lifetime history of alcohol dependence (Watson, Detra, Fox, & Ewing, 1995). Elevated MAST scores have also been found to be associated with recidivism among various groups of sexual offenders (Firestone et al, 1998(Firestone et al, , 1999.…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…Watson et al. () also suggested that 6/7 was the optimal cutoff point for the MAST, yielding a sensitivity of 0.92 and a specificity of 0.87. These findings are similar to the results of the present study, justifying an optimal cutoff point of 6/7 for the MAST‐C to identify patients with alcoholism.…”
Section: Discussionmentioning
confidence: 99%